On Comparing the Time Resolution of Proposed Complex Wavelet With Morlet - Narsimulu, Gaddam; Reddy, B. Krishna (Communications in Mathematics and Applications, 2022)
In this study, we compare the complex Morlet wavelet’s time-frequency resolution to that of a proposed complex continuous wavelet. The proposed complex continuous wavelet has a substantially lower time resolution than the complex Morlet wavelet. As a result, the proposed complex continuous wavelet is appropriate for applications requiring high time resolution. The efficiency of the proposed complex wavelet over the complex Morlet wavelet in evaluating the QRS complex and R-peak in ECG signals is demonstrated.